2011
DOI: 10.1055/s-0031-1297115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benidipine Hydrochloride on Autonomic Nervous Activity in Hypertensive Patients with Highand Low-salt Diets

Abstract: Key wordsBenidipine hydrochloride, autonomic nerve, essential hypertension, high-or lowsalt diet CAS 91559−74−5 Coniel  Hypertension, essential Arzneim.-Forsch./Drug Res. 53, No. 5, 314−320 (2003) SummaryThe effects of benidipine hydrochloride (CAS 91559-74-5, Coniel  ) on autonomic nervous activity in hypertensive patients with high-and low-salt diets were investigated. Six patients having a urinary sodium excretion of 80 mEq/day or less (low salt group) and 6 patients having a urinary sodium excretion of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As shown in Figure 4, benidipine lowers blood pressure more slowly than nifedipine, and the extent of reflex tachycardia by benidipine is about half of that by nifedipine [57]. Clinical studies have demonstrated that benidipine either has no effects on heart rate or LF/HF ratio [62,71–73] or increased the heart rate [74,75]. Efonidipine is known as a dual L‐ and T‐type Ca 2+ channel blocker, which is clinically available in Japan.…”
Section: Classification Of Ca2+ Channel Blockersmentioning
confidence: 99%
“…As shown in Figure 4, benidipine lowers blood pressure more slowly than nifedipine, and the extent of reflex tachycardia by benidipine is about half of that by nifedipine [57]. Clinical studies have demonstrated that benidipine either has no effects on heart rate or LF/HF ratio [62,71–73] or increased the heart rate [74,75]. Efonidipine is known as a dual L‐ and T‐type Ca 2+ channel blocker, which is clinically available in Japan.…”
Section: Classification Of Ca2+ Channel Blockersmentioning
confidence: 99%
“…Diltiazem does not affect NO production [13], whereas benidipine stimulates NO production [14][15][16] to a larger extent than other CCBs [14], thereby increasing coronary blood flow and improving ischemic myocardial metabolism and cardiac function [15]. Benidipine has a slow vasodilating activity [17], without stimulating sympathetic activity [18], reducing afterload and cardiac index in hypertensive patients [19]. Moreover, benidipine exhibited a protective effect through NO production and antioxidant activity on the ischemic myocardium in an ischemic reperfusion injury animal model (rabbit) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Switching from cilnidipine to benidipine in this study did not cause heart rate increase, tachycardia or facial flush, indicating the maintenance of N-type calcium channel blocking activity. Benidipine is reported to block the N-type calcium channel [20] and inhibit the sympathetic nervous system [28,29]. In investigational and post-marketing clinical trials, benidipine induced tachycardia, facial flush and hot flush in 0.03 %, 0.34 % and 0.17 %, respectively, while cilnidipine induced these side effects in 0.02 %, 0.46 % and 0.16 %, respectively.…”
Section: Renal Protective Effects Of Benidipine and Its Mechanismsmentioning
confidence: 99%